Abstract 175: Impact of COVID‐19 on Intracranial Aneurysm Treatment and Outcomes: A Nationwide Propensity Score Matched Study. - Jorge R. Rios Zermeno; Abdul Karim A. Ghaith; Victor G. El‐Hajj; Loizos Michaelides; Rabih G. Tawk (Stroke: Vascular and Interventional Neurology)
Introduction The coronavirus disease 2019 (COVID‐19) pandemic has had a global impact on healthcare systems. There is limited data on the influence of COVID‐19 on treatment and outcomes in patients with intracranial aneurysms. We aimed to investigate the impact of COVID‐19 on the overall complications, including ischemic stroke and subarachnoid hemorrhage (SAH) rates in patients treated for intracranial aneurysms (IAs). Methods This national, multicenter, retrospective cohort study included patients diagnosed and treated for IAs from January 2016 to December 2020 in the National Inpatient Sample (NIS). A total of 57,715 admissions were identified. Of these, 45,979 occurred pre‐COVID and 11,736 during the COVID pandemic period. The outcome data points included the occurrence of postprocedural ischemic strokes or SAHs, death, non‐routine discharge, total charges (US dollars), and length of stay (days). A 1:1 propensity score matching protocol was applied using a K‐nearest neighbor approach to evaluate differences in the outcome data points between the pre‐COVID and during COVID periods. The trends during the study period were assessed using piecewise joinpoint regression with the Mann‐Kendall test. Results Overall, the mean age was 65 years, with most of the patients (69.9%) being females. Endovascular interventions were performed in 82.9% of pre‐COVID IAs admissions compared to 82.4% during the COVID period, while open surgical treatment was performed in 17.1% of pre‐COVID and 17.6% of the patients during COVID (p=0.625). After matching, there were no differences in length of stay (p=0.266), non‐home discharge (p=0.475), and in‐hospital mortality rates (p=0.305) between the two periods; however, the overall complication rate was significantly higher during the pandemic (31.1% vs. 28.3%; p<0.001). From 2016 to 2020, an upward trend in hospitalizations for ischemic stroke was seen among patients treated for IAs (6.1% to 7.9%; p=0.04). No trends were observed with respect to the occurrence of SAH or death (p=0.31). Patients hospitalized after treatment of IAs during the COVID pandemic had significantly higher odds of ischemic strokes (OR 1.13; 95% CI 1.05 to 1.22; p=0.03) but not SAH (OR 0.97; 95% CI 0.88 to 1.06; p=0.89). Conclusion The COVID‐19 pandemic has significantly impacted the healthcare system. In patients receiving treatment for IAs, this analysis noted a correlation between the COVID‐19 pandemic and postoperative complications, notably ischemic strokes. Unraveling the pandemic’s “black box” leads to awareness of plausible breaches within the system, which acts as a crucial component in improving situational readiness and preparedness in the event of similar large‐scale crises.